Answer:
y=-4x+9
Step-by-step explanation:
y-y1=m(x-x1)
y-(-3)=-4(x-3)
y+3=-4(x-3)
y=-4x+12-3
y=-4x+9
Answer:
You can't get a square root of any number that has a negative sign on the inside of the radical
Answer:
7
Step-by-step explanation:
The rate of change is defined as
f(x2) - f(x1)
--------------------
x2-x1
x2 = 6
f(6) = x^2 – 3x – 10 = 6^2 -3*6 -10 = 36 - 18-10=8
x1 = 4
f(4) = x^2 – 3x – 10 = 4^2 -3*4 -10 = 16 - 12-10=-6
Substitute the values into the expression
8 - -6
--------------------
6-4
8+6
------------
2
14/2= 7
Answer: 340 centimeters
Step-by-step explanation: Just times 3.4 by 10 to get 340 centimeters.
Hope this helped!
Please mark brainliest if you feel like it!
Answer:
106
Step-by-step explanation:
1272/21